Impact of rituximab regime on time to relapse in aquaporin-4 antibody positive neuromyelitis spectrum disorder. Issue 9 (12th August 2022) - Nasir, Moneeb; Hone, Luke; Palace, Jacqueline; Tallantyre, Emma; Kelly, Patricia; Isabel Leite, M; Robertson, Neil; Bestwick, Jonathan; Huda, Saif; Dobson, Ruth
Abstract : Background: Aquaporin-4 (AQP4) antibody associated neuromyelitis optica spectrum disorder (NMOSD) requires long-term immunomodulation. In refractory cases rituximab can be used, however the optimal regime is not established. Methods: We retrospectively examined different rituximab regimes in AQP4-NMOSD. Standard mono- therapy (SM; 6 monthly infusions), SM plus oral steroids (SM+S), extended interval dosing (EID; with retreat- ment at CD19 >1%) and EID with oral steroids (EID+S) were compared. The primary outcome was time to first clinical relapse. Potential confounders including age, gender, number of previous relapses, and onset phenotype were included. Results: 77 patients were included: 67 females, mean age 34.6, median DSS at rituximab initiation 5.0. 40 were on SM+S, 19 on SM, 8 on EID, and 10 on EID+S, with mean follow-up 38.5 months. 25/77 patients relapsed on rituximab. Median time to first relapse was 39 months (SM+S), 46 months (SM), 54 months (EID) and 42 months (EID+S). Adjusted Cox proportional hazard model revealed no significant difference between rituximab regimes (SM+S as reference; hazard ratio for SM 1.39, 95%CI 0.49–4.1, p=0.55; hazard ratio for EID 0.70, 95%CI 0.15–3.3, p=0.65; hazard ratio for EID+S 1.63, 95%CI 0.48–5.5, p=0.43). 9 significant infections were recorded, 3 in the SM group and 6 in SM+S. Conclusions: This provides initial evidence that EID could be used for long term treatment of NMOSD. This may improve patient experience and consolidate use of hospital resources.